(3SbW GdBd aj TYQ GdBd (B((3Bd GdHjJ GdCWgGQ(B)s - (3ESeGYjd Hf eMeO Hf GdMSf Hf GdbGSe GdMSfj GdWGdHis; (3GdeJhcd Ydj Gddg , ESeGYjd Hf GdbGSe Hf eMeO,J (B1087 (3g` s ((3eOjfI UfYGA s)
(3ChdgG (B:s
(3hHYO aEfi deG QCjJ cKjQkG ef GdfGS bO PcQhG VQhHkG ef GdBOGH hVefhG eDdaGJge ef Pdc GdYde GdYLH GdYLGH s
(3BNQgG (B:s
(3dcfg HeMGSf YQVg jYdh HgG bOQkG Ydi GdCbQGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdChQGb GdChdi hGdNjQI ePgHg ehTGIs
(3hGdYfhGfGJ cJHJ HCdhGf eNJdaI hHChdgG agQS ddehVhYGJ HNW eZGjQhHgG HYV JbWjYs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B287s
Keywords: (3GdCOHs